MULTIMEDIA EDITOR OF VIRTUAL PHYSICAL LABORATORY IN DISTANCE LEARNING SYSTEM «KHERSON VIRTUAL UNIVERSITY» - Kravtsov Г.М.; Baiev А.С.; Lemeshchuk О.І.; Orlov В.В. (Journal of Information Technologies in Education (ITE), 2017)
The questions of modeling the structure of the objects of the system, the design of software modules and technologies for creating the editor of a virtual laboratory are considered. The relevance of the study is due to the lack in existing distance learning systems of support for the creation and use of virtual laboratory work on disciplines of the natural-science profile. The subject of the study is a software module for creating and using virtual laboratory work in a distance learning system. The purpose of the study is the development of a system model and a description of the software development technology of a virtual laboratory for physics for a distance learning system. The information technologies of designing the structure of the virtual laboratory and the main modes of the program module of the editor of the virtual laboratory work are described. At the heart of the structure of the software module "Virtual Laboratory" is the multimedia Web-editor of virtual laboratory works, which is created using object-oriented design technology. The program library of multimedia 3D objects created in the development environment of interactive graphic objects Unity3D. It unifies the process of creation and processing of virtual laboratory works. The basic mathematical package for supporting calculations is the mathematical processor Waterloo Maple. The application of the developed software interface will allow teachers to create laboratory works and use them in their distance courses. Students, in turn, will be able to conduct research, performing virtual laboratory work. As an example, the editor of the virtual laboratory for physics in the distance learning system "Kherson Virtual University" is considered.